In Vitro Cytotoxicity Evaluation of Nanosized Hydroxyapatite and Fluorapatite on Cell Lines and Their Relevance to the Alveolar Augmentation Process - Wojciech Zakrzewski; Maria Szymonowicz; Anna Nikodem; Agnieszka Rusak; Zbigniew Rybak; Katarzyna Szyszka; Dorota Diakowska; Benita Wiatrak; Rafal J. Wiglusz; Maciej Dobrzyński (Journal of Functional Biomaterials)
Background/Objectives: Materials with an apatite structure were investigated in vitro in dental bone augmentation procedures. This scientific study aimed to compare nanosized hydroxyapatite (nHAp) and fluorapatite (nFAp) materials in the form of tablets in in vitro studies, including cytotoxicity assessment and fluoride release. Methods: The nHAp and nFAp nanosized materials were obtained using the microwave hydrothermal method. Subsequently, the tablets were prepared from these nanosized powders as further studied materials. Cytotoxicity tests were conducted on Balb/3T3 fibroblast cells and L929 cells. Fluoride ion release was tested at 3, 24, 48, 72, and 168 h periods. Results: Both materials presented viability levels above 70%, indicating a lack of cytotoxic potential. The amount of fluoride (F−) ions released and accumulated from nFAp was greatly higher than from nHAp. The release of F− ions in both samples was the highest in the first 3 h of exposition. The accumulation of F− ions reached the highest values in the deionized water. The most significant differences in the released or cumulated fluoride ions were observed between deionized water and lower 4.5 pH AS (artificial saliva) samples. Conclusions: Both nanosized hydroxyapatite and fluorapatite materials are biocompatible, and their in vitro examination showed promising results for their future in vivo application.